Application Method Learning Discovery Learning on Eye Lesson Economy in Increase Interest and Results Study Student - Aslamiah; Harahap, Fitriani (Journal of General Education Science, 2024)
This research aims to increase student interest and learning outcomes. This type of research is classroom action research (PTK), with qualitative methods that explore a concept in a research problem. The research location was carried out at SMPN 5 Satu Muara Batang Girls Roof in December- January Research subjects used is a class VII student population of 21 students, with a research sample of 21 student. Student learning outcomes have improved by using the learning modelDiscovery Learning. With the results, the average student score was 84.7619 students who received the value above the KKM has exceeded 75% namely 19 students while students who got marks under KKM as much 2 students with presentations 20. The highest value is 100 and value Lowest 60.